Obstructive sleep apnea in patients with type 2 diabetes mellitus in Egyptian population - Rania Ahmad Sweed; Nashwa Hassan Abd El Wahab; Mona Saeed El Hooshy; Eman Youssef Morsy; Dina Mohsen Shetta (The Egyptian Journal of Bronchology, 2023)
Abstract Background Sleep disordered breathing (SDB) is a widespread disorder with a wide range of harmful outcomes including obstructive sleep apnea (OSA), central sleep apnea (CSA), or sleep-related hypoventilation. Purpose The aim of the present study was to screen for the occurrence of sleep apnea syndrome in patients with type 2 diabetes mellitus (DM) and to evaluate the relation between the presence of sleep apnea and the level of glycemic control. Methods This was a prospective clinical study that enrolled 59 patients who were previously diagnosed as type 2 DM. Sleep study level IV was done using overnight recording of oxygen saturation and pulse. Results Among the studied patients, 42 were females and 17 were males, Their mean age was 59.76 ± 11.13 years. Obstructive sleep apnea was diagnosed in 46 patients (78%). Thirty three (86.8%) patients among those with uncontrolled glycemic level were diagnosed as OSA, whereas 13(61.9%) patients with controlled glycemic level were diagnosed as OSA showing statistically significant difference, p = 0.047. There was no correlation between either HbA1c, age, Mallampati score, or BMI and ODI but there was a correlation between STOP-BANG questionnaire and ODI (P = 0.036). The variables that were significantly related to presence of OSA, were comorbidities, ESS, Mallampati score, STOP-BANG, and sleep symptoms (nocturia and snoring) P value (0.029), (0.031), (0.022), (0.005), (0.049), and (0.012), respectively. Conclusion Patients with type 2 diabetes showed a significant high prevalence of OSA. With significant higher prevalence among patients with uncontrolled DM versus controlled DM.